Construct validity of the Amsterdam Preoperative Anxiety and Information Scale (Italian Version) in women undergoing breast biopsy: a brief research report - Miraglia Raineri, Alessandra; Pelagotti, Stefania; Lauro-Grotto, Rosapia (Acta Biomedica Atenei Parmensis, 2019)
The goal of this paper was to test Construct Validity of the Amsterdam Preoperative Anxiety and Information Scale (Italian Version) in women undergoing Breast Biopsy. To answer this purpose we have utilized Exploratory Factor Analysis (EFA) in a sample of 80 women undergoing Breast Biopsy at the Breast Unit of the Careggi University Hospital in Florence from January to February 2015. Overall the results support the construct validity of the Italian version of the APAIS for the population of women undergoing Breast Biopsy suggesting that the Italian version of APAIS can be useful to detect this clinically very relevant dimension.